solution_c1pdf - armington (kma786) 4.9 Stepp (55860) 1...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: armington (kma786) 4.9 Stepp (55860) 1 This print-out should have 10 questions. Multiple-choice questions may continue on the next column or page find all choices before answering. 001 10.0 points Find the value of f (0) when f ( t ) = sin 2 t , f parenleftBig 2 parenrightBig = 5 . 1. f (0) = 1 2. f (0) = 2 3. f (0) = 0 4. f (0) = 4 correct 5. f (0) = 3 Explanation: Since d dx cos mt = m sin mt , for all m negationslash = 0, we see that f ( t ) = 1 2 cos 2 t + C where the arbitrary constant C is determined by the condition f ( / 2) = 5. But cos 2 t vextendsingle vextendsingle vextendsingle t = / 2 = cos = 1 . Thus f parenleftBig 2 parenrightBig = 1 2 + C = 5 , and so f ( t ) = 1 2 cos 2 t + 9 2 . Consequently, f (0) = 4 . 002 10.0 points Find the value of f ( 1) when f ( t ) = 18 t 2 and f (1) = 5 , f (1) = 6 . Correct answer: 4. Explanation: The most general anti-derivative of f has the form f ( t ) = 9 t 2 2 t + C where C is an arbitrary constant. But if f (1) = 5, then f (1) = 9 2 + C = 5 , i . e . C = 2 . Thus f ( t ) = 9 t 2 2 t 2 , from which it follows that f ( t ) = 3 t 3 t 2 2 t + D , where the constant D is determined by the condition f (1) = 3 1 2 + D = 6 , i . e . D = 6 . Consequently, f ( t ) = 3 t 3 t 2 2 t + 6 , and so at t = 1, f ( 1) = 4 . 003 10.0 points Find the unique anti-derivative F of f ( x ) = e 3 x + 3 e 2 x + 2 e x e 2 x for which F (0) = 0. 1. F ( x ) = e x + 3 x e x 2. F ( x ) = 1 3 e 3 x + 3 x 2 3 e 3 x 1 3 armington (kma786) 4.9 Stepp (55860) 2 3. F ( x ) = 1 3 e 3 x 3 x + e x 1 3 4. F ( x ) = e x + 3 x 2 3 e 3 x 1 3 correct 5. F ( x ) = e x 3 x + 2 3 e 3 x + 5 3 6. F ( x ) = e x 3 x + 2 3 e x + 1 3 Explanation: After division, e 3 x + 3 e 2 x + 2 e x e 2 x = e x + 3 + 2 e 3 x . Since d dx e x = e x , it thus follows that F ( x ) = e x + 3 x 2 3 e 3 x + C where the constant C is determined by the condition F (0) = 0. For then F (0) = 1 2 3 + C = 0 ....
View Full Document

Page1 / 7

solution_c1pdf - armington (kma786) 4.9 Stepp (55860) 1...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online